2019
DOI: 10.1021/acsmedchemlett.9b00095
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Loop: Developing an Integrated Design, Make, and Test Platform for Discovery

Abstract: The relatively slow cycle time within medicinal chemistry from synthesis to assay is constantly being challenged to help improve the efficiency of the discovery process. While both synthesis and assay have been automated to varying degrees, there has, until recently, been limited focus on the complete design, make, and test process. This Innovations article outlines the development of Cyclofluidic from inception through to the commercialization of a fully integrated closed loop design, synthesis, and screen pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…The stability factors in the hanging drop network were the speed of flow and droplet radii. The computer simulation results showed that the taper-tube culture method used a deeper flow tube and had a lower curvature interface that caused higher stability of droplet [10,37]. In the taper-shaped microfluid chip, the suspension unit had a hole with a narrow upper and lower width and the cross-section formed a wedge shape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability factors in the hanging drop network were the speed of flow and droplet radii. The computer simulation results showed that the taper-tube culture method used a deeper flow tube and had a lower curvature interface that caused higher stability of droplet [10,37]. In the taper-shaped microfluid chip, the suspension unit had a hole with a narrow upper and lower width and the cross-section formed a wedge shape.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the curve of the water volume fraction as a function of time, the taper-shaped tray was relatively efficient. For liquid exchange, the effectiveness and the efficiency of the medium exchange process were determined by observing the volume fraction changes in moisture in the simulation area at different time points [37]. Combined with the peristaltic pump, the taper-shaped tray was found to be more efficient discharged liquid from the outlet at a constant rate to achieve liquid exchange that can effectively solve the disadvantages of the traditional hanging drop culture method which cannot replace the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports show how appealing flow chemical processes are nowadays, in what concerns safety (the need to handle hazardous, toxic or labile chemicals can be avoided), process scale‐up ability (most of the times it is more straightforward than with conventional methods) and profitability (high‐value products can be obtained in a 24/7 manner, due to high levels of automatization, inline quality control technologies and purification techniques). Furthermore, other well‐established techniques can be coupled with continuous‐flow setups, allowing the development of automated drug discovery platforms . Consequently, the future of flow chemistry might be oriented to the ability to increase new molecule output of drug discovery programs, while facilitating and accelerating the identification of hit compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The potential value of automated design-make-test-analyze (DMTA) cycles in drug discovery is substantial 126,183 . Benefits of automation include 131 :…”
Section: Box 5 Reducing Cycle Times By Automationmentioning
confidence: 99%